Impact of cross-border electricity trading on regional market participants : : doctoral thesis - Andročec, Ivan (I. Andročec ; Fakultet elektrote hnike i računarstva, 2012)
SUMMARY: Research and development of broader picture of impact technical and economical elements in cross-border electricity trade and trading mechanisms (congestion, transit) which influence on competitivity and planning of different market participants (generators/traders, transmission system operators, suppliers/buyers). It is shown that market coupling of areas in regional market can make positive and negative impacts on participants behaviour. It is modelling and analyzing imaginary market through different programs like MATLAB, EMCAS, MASI with presumption that we have four connected areas in market and common power exchange. Coordinated regional congestion and ITC mechanisms can bring increased competition, interconnection usage and decrease of market participants risks. Efficient cross-border electricity trade increase regional market integration. For more benefits from electricity trade we need more investments. It is shown that sometimes for that we do not have clear market signals. Interactions between decentralised decisions of participants and mechanisms have different costs and benefits for participants. Scientific research contribution is in next: * methodology of market coupling/splitting for eficient electricity trading, * algorithm for optimization of benefits/costs from electricity transit in inter area trading * choice of additional criteria for optimal power system expansion and * methodology of risk calculation for few trading areas. -